La despensa nacional: Quinoa and the Spatial Contradictions of Peru’s Gastronomic Revolution - Emma McDonell (Latin American Research Review, 2024)
This article explores the spatial politics of Peru’s gastronomic revolution and corresponding efforts to territorialize Peruvian agricultural products by tracing the spatial dynamics of quinoa’s trajectory from highland dietary staple to coveted national food. Efforts to codify Peru’s national cuisine have involved mapping ingredients and dishes onto specific regions while dramatically reshaping agricultural production geographies and culinary topographies. Because of quinoa’s success as a high-value export crop, the Peruvian altiplano is no longer perceived as a landscape useful exclusively for livestock pasture and mining. Instead, it is imagined as agriculturally productive: the country’s quinoa heartland. At the same time, quinoa’s trajectory illuminates spatial contradictions in the gastronomic boom’s purported objectives and its tangible effects. The revalorization of quinoa led to a geographical expansion of its production outside the high Andes, undermining the spatially bound concepts of authenticity promoted by gastronomic leaders in Peru. Broadly, efforts to commercialize marginalized food products and their corresponding regions can at once reconfigure territorial discourses in important ways, reinforce long-standing geographical inequalities, and generate contestations of the geographic imaginaries of food and nation.